Age effects on measurements of hypothalamic-pituitary-adrenal axis activation in laying hens - Meagan E. Abraham; Priscila Serpa; Gregory S. Fraley; Darrin M. Karcher (Poultry Science)
Stress is a complex but poorly understood topic, especially in commercial poultry species. However, hypothalamic-pituitary-adrenal axis (HPA) activation through either exogenous glucocorticoid or adrenocorticotropic hormone (ACTH) administration in birds generally results in increased circulating glucocorticoid levels, often associated with stress. HPA activation responses are complicated by physiological changes while the birds mature and enter production. The objective of this study was to evaluate changes in HPA activation in relation to physiological age of the bird. Ten each of Lohmann LSL-Lite hens received either a saline-mannitol or synthetic ACTH (ACTH1-24) injection at 6, 17, and 26 weeks of age (WOA). Blood was collected prior to ACTH injections, and one-, and two-hours post-injection. From these blood samples, white blood cell (WBC) differential counts, heterophil:lymphocyte (H:L) ratios (N = 10/treatment), and corticosterone and cortisol levels were measured using a high-performance liquid chromatography (HPLC) system coupled to a mass spectrometer (MS/MS) (N = 5/treatment). At 26 weeks of age, egg albumen samples were collected and corticosterone and cortisol measured using an HPLC system coupled to a mass spectrometer (MS/MS) (N = 5/treatment). In this study, plasma cortisol was unaffected by treatment and egg albumen corticosterone and cortisol were below detectable limits at all time points for both treatments. Plasma corticosterone increased 1 h after injection in the ACTH group at all ages; this was significant at 17 WOA (P < 0.0001). The H:L ratio was not affected by treatment but heterophils increased and lymphocytes decreased in the ACTH group compared to the control group, this difference was observed at 26 WOA (P < 0.0004). The results of this study suggest that the H:L ratio is not an accurate measure of acute HPA activation during the pullet phase and that plasma cortisol and albumen corticosterone and cortisol are not an accurate measure of acute HPA activation during the pullet or adult phases. Corticosterone may have some utility in capturing a physiological stress response in pullets and adult hens but requires further investigation.